(untitled) (Fiep Bulletin - online, 2014)
After deep changes in all its political system, Slovakia has also undergone great transformations in Education in general, and in School Physical Education, in especial. The new conception about School Physical Education is based on ideas such as democracy, humanism and freedom. Students’ emotion-oriented, intellect-guided aspects, creativity, socialization, motivation and engaging process are also important in the new concepts. The development of physical and motor basic competence and the learning of motor and knowledge skills have remained relevant objectives of School Physical Education. On the other hand, students’ assessment, the maintenance of students’ interest level, research, management and teachers’ qualification are considered the high points of the Physical Education process in that country. The author concludes that Physical Education in Slovakia reflects its society problems.